2018
DOI: 10.1149/2.0441811jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition, Microstructure and Magnetic Properties of Nickel-Cobalt-Copper Alloy Powders

Abstract: Powders of Ni-Co alloys containing small amounts of Cu were produced by electrodeposition from an ammonium bath. Cathodic polarization curves were recorded and partial current densities for alloy deposition and hydrogen evolution were determined. At a current density of 100 mA cm −2 , the electrodeposition process resulted in Ni 79.1 Co 18.6 Cu 2.3 powder with an average grain size of 6.8 nm, composed of an amorphous matrix and FCC nanocrystals. The deposition of Cu with Ni and Co led to a higher proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…An increase in the Cu content in the metal powder promotes the nanoparticles' self-sintering and the further coalescence of the obtained ternary alloy powder-possibly due to its lower melting point (see Table 3). A similar phenomenon was observed by [20] as it is reported that the presence of copper may cause a nucleation effect during deposition. The elemental mapping of the 10Cu80Ni10Co metallic powder reduced at 300 • C is shown in Figure 9.…”
Section: Characterization Of Ternary Alloy Metallic Powderssupporting
confidence: 83%
See 3 more Smart Citations
“…An increase in the Cu content in the metal powder promotes the nanoparticles' self-sintering and the further coalescence of the obtained ternary alloy powder-possibly due to its lower melting point (see Table 3). A similar phenomenon was observed by [20] as it is reported that the presence of copper may cause a nucleation effect during deposition. The elemental mapping of the 10Cu80Ni10Co metallic powder reduced at 300 • C is shown in Figure 9.…”
Section: Characterization Of Ternary Alloy Metallic Powderssupporting
confidence: 83%
“…This result suggests that the three metal powders, under these compositions, may constitute a single FCC phase, with the same matrix as in the three alloys. The same XDS result for a Cu-Ni-Co alloy produced by different methodologies can be found in the literature, where it the presence of a similar FCC phase is mentioned [6,8,11,14,19,20]. The calculations of the Rietveld method were not accomplished due to the lack of reported phases that contain these elements (Cu, Ni and Co) in the Inorganic Crystal Structure Rietveld's Database (ICSD).…”
Section: Characterization Of Ternary Alloy Metallic Powdersmentioning
confidence: 83%
See 2 more Smart Citations
“…Electrodeposition of the binary Ni−Co system has been studied comprehensively, mainly due to its importance in the soft magnetism field [37,38]. The possibility to obtain different nanostructures and/or morphologies provides an excellent opportunity for establishing correlations between structure and magnetism of these alloys, and consequently to tailor their magnetic properties.…”
Section: Introductionmentioning
confidence: 99%